2012
DOI: 10.1007/s00707-012-0618-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pulse chaotic dynamics of non-autonomous nonlinear system for a honeycomb sandwich plate

Abstract: The global bifurcations and multi-pulse chaotic dynamics of a simply supported honeycomb sandwich rectangular plate under combined parametric and transverse excitations are investigated in this paper for the first time. The extended Melnikov method is generalized to investigate the multi-pulse chaotic dynamics of the non-autonomous nonlinear dynamical system. The main theoretical results and the formulas are obtained for the extended Melnikov method of the non-autonomous nonlinear dynamical system. The nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In the study, the influences of the structural parameters on the dimensionless linear natural frequencies of the truss core sandwich beam are studied at first by neglecting the nonlinear terms in (20). The face sheets and the truss of the sandwich beam are made of the same material.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study, the influences of the structural parameters on the dimensionless linear natural frequencies of the truss core sandwich beam are studied at first by neglecting the nonlinear terms in (20). The face sheets and the truss of the sandwich beam are made of the same material.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…represents the coupled relation between the different modes and the coupled term does not appear when the single mode response is considered. The coefficients in (20) are presented in the Appendix.…”
Section: Nonlinear Frequency Response Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [14] studied the free vibration of the sandwich plate with square honeycomb cores by using a semi-analytical method. Zhang et al [15] investigated the global bifurcations and multi-pulse chaotic dynamics of a simply supported honeycomb sandwich rectangular plate by using the extended Melnikov method.…”
Section: Introductionmentioning
confidence: 99%
“…We have found two papers on bifurcations and chaotic dynamics of sandwich plates. J.H.Zhang and W. zhang [9] investigated the global bifurcations and multi-pulse chaotic dynamics of a simply supported honeycomb sandwich rectangular plate under combined parametric and transverse excitations, they found that multi-pulse chaotic motions can occur in the honeycomb sandwich rectangular plate. Applying the Galerkin's approach, Zhang et al [10] investigated nonlinear dynamic behaviors of a simply supported 3D-Kagome truss core sandwich plate subjected to the transverse and the inplane excitations.…”
Section: Introductionmentioning
confidence: 99%